Nanoscale single crystal thin film

By introducing a transition layer containing H elements between the single crystal film and the substrate, the problem of insufficient bonding force between the single crystal film and the substrate is solved, and a higher bonding force and higher yield are achieved.

CN108539009BActive Publication Date: 2025-04-04JINAN JINGZHENG ELECTRONICS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN201810644600.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-10-13
Filing Date
2018-06-21
Publication Date
2025-04-04
Estimated Expiration
2038-06-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the bonding force between a single crystal film and a substrate, resulting in large-area debonding in the device cutting process, affecting the yield rate.

Method used

A nano-scale single crystal thin film structure is adopted, including a nano-scale single crystal thin film layer, an isolation layer, a substrate layer, and the first and second transition layers. The first transition layer is located between the nano-scale single crystal thin film layer and the isolation layer, containing a certain concentration of H elements, and the second transition layer is located between the isolation layer and the substrate layer. These transition layers release stress, reduce defects, and improve bonding force.

Benefits of technology

By enhancing the bonding force between the single crystal film and the substrate, large-area debonding phenomenon in the cutting process is avoided, and the utilization rate of nano-scale single crystal films and the yield rate of the device are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN108539009B_ABST
    Figure CN108539009B_ABST
Patent Text Reader

Abstract

A nanoscale single crystal film is provided. The nanoscale single crystal film comprises a nanoscale single crystal film layer, a first transition layer, an isolation layer, a second transition layer and a substrate layer, wherein the first transition layer is located between the nanoscale single crystal film layer and the isolation layer, and the second transition layer is located between the isolation layer and the substrate layer, wherein the first transition layer contains a certain concentration of H element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nanometer-scale single crystal film, in particular to a nanometer-scale single crystal film comprising a film layer with a thickness of 10nm to 2000nm. Background Art

[0002] Oxide single crystal films such as lithium tantalate single crystal films and lithium niobate single crystal films are widely used as piezoelectric materials in surface acoustic wave (SAW) components due to their large electromechanical coupling coefficient. They have a wide range of uses in optical signal processing, information storage, and electronic devices. They can be used as basic materials for preparing high-frequency, high-bandwidth, high-integration, large-capacity, low-power optoelectronic devices and integrated optical circuits.

[0003] As the demand for reducing device power consumption, reducing device size and improving device integration becomes higher and higher, the thickness of wafers is becoming thinner and thinner. Summary of the invention

[0004] Exemplary embodiments of the present invention provide a nanoscale single crystal thin film that can improve the bonding force between the single crystal thin film and a substrate.

[0005] An exemplary embodiment of the present invention provides a nanoscale single crystal film, which may include a nanoscale single crystal film layer, an isolation layer, a substrate layer, a first transition layer and a second transition layer, wherein the first transition layer is located between the nanoscale single crystal film layer and the isolation layer, and the second transition layer is located between the isolation layer and the substrate layer, wherein the first transition layer contains a certain concentration of H element.

[0006] According to an exemplary embodiment of the present invention, the first transition layer may further include elements used in plasma treatment, such as Ar, N, etc.

[0007] According to an exemplary embodiment of the present invention, the concentration of H element in the first transition layer may be 1×10 19 atoms / cc~1×10 22 atoms / cc.

[0008] According to an exemplary embodiment of the present invention, the material of the nano-scale single crystal thin film layer may be lithium niobate, lithium tantalate or quartz, and the thickness of the nano-scale single crystal thin film layer may be 10 nm to 2000 nm.

[0009] According to an exemplary embodiment of the present invention, the material of the substrate layer may be lithium niobate, lithium tantalate, silicon, quartz, sapphire or silicon carbide, and the thickness of the substrate layer may be 0.1 mm to 1 mm.

[0010] According to an exemplary embodiment of the present invention, the isolation layer may be a silicon dioxide layer, the thickness of the isolation layer may be 0.05 μm to 4 μm, the thickness of the first transition layer may be 2 nm to 10 nm, and the thickness of the second transition layer may be 0.5 nm to 15 nm.

[0011] According to an exemplary embodiment of the present invention, the thicknesses of the first transition layer and the second transition layer may be different.

[0012] According to an exemplary embodiment of the present invention, the material of the nano-scale single crystal thin film layer and the material of the substrate layer may be the same.

[0013] According to an exemplary embodiment of the present invention, the material of the nano-scale single crystal thin film layer and the material of the substrate layer may be different.

[0014] According to an exemplary embodiment of the present invention, in the direction from the nanoscale single crystal thin film layer to the isolation layer, the content of the nanoscale single crystal thin film layer elements in the first transition layer can gradually decrease, and the content of the isolation layer elements can gradually increase; in the direction from the isolation layer to the substrate layer, the content of the isolation layer elements in the second transition layer can gradually decrease, and the content of the substrate layer elements can gradually increase.

[0015] According to an exemplary embodiment of the present invention, the H element in the first transition layer may have a maximum concentration, and the concentration of the H element in the first transition layer may gradually decrease from the maximum concentration toward the isolation layer and the nanoscale single crystal thin film layer.

[0016] According to an exemplary embodiment of the present invention, the first transition layer and the second transition layer of the nanoscale single crystal film can release stress, reduce defects in the single crystal film and the isolation layer, improve the quality of the single crystal film and the isolation layer, and can play a role in reducing transmission losses; in addition, releasing stress can make the medium at the interface more uniform, reduce the scattering of light during propagation, and thus reduce transmission losses.

[0017] According to an exemplary embodiment of the present application, the H element in the first transition layer is beneficial to improving the bonding strength of the single crystal film. When the nanoscale single crystal film is used to prepare a filter device for a cutting process, a large-area debonding phenomenon can be avoided, thereby increasing the utilization rate of the nanoscale single crystal film and further improving the yield of the filter device. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The above and other objects and features of the present invention will become more apparent through the following description of exemplary embodiments in conjunction with the accompanying drawings, in which:

[0019] Figure 1 is a schematic diagram showing a nanoscale single crystal thin film according to an exemplary embodiment of the present invention;

[0020] Figure 2 is shown with Figure 1 Transmission electron microscope (TEM) image of nanoscale lithium tantalate single crystal thin film (LTOISI) on silicon substrate corresponding to the nanoscale single crystal thin film;

[0021] Figure 3 and Figure 4 They are Figure 2 TEM magnified images of area A and area B;

[0022] Figure 5 is the secondary ion mass spectra (SIMS) of LTOISI;

[0023] Figure 6 and Figure 7 They are the element distribution maps of the bonding surface and deposition surface of LTOISI;

[0024] Figure 8 is shown with Figure 1 Transmission electron microscope (TEM) image of nanoscale lithium niobate single crystal thin film (LNOI) on lithium niobate substrate corresponding to the nanoscale single crystal thin film;

[0025] Fig. 9 and Fig.10 They are Figure 8 TEM magnified images of area C and area D;

[0026] Fig.11 is the secondary ion mass spectrometry (SIMS) of LNOI;

[0027] Fig.12 and Fig.13 The element distribution maps of the bonding surface and deposition surface of LNOI respectively; and

[0028] Fig.14 is a schematic diagram showing a bonding force test experiment performed on an LTOISI sample according to an exemplary embodiment. DETAILED DESCRIPTION

[0029] Now, reference will be made in detail to the embodiments and methods of the present invention, which constitute the best mode of practicing the present invention currently known to the inventors. However, it should be understood that the disclosed embodiments are merely illustrative of the invention that can be implemented in various alternative forms. Therefore, the specific details disclosed herein should not be construed as limiting, but are only representative bases for any aspect of the invention and / or for teaching those skilled in the art to apply the present invention in various forms.

[0030] The traditional grinding and thinning process can thin the single crystal film to a few microns to tens of microns, but this method not only requires sacrificing most of the thickness of the wafer and increasing the production cost, but also the single crystal film with micron-level thickness can no longer meet the requirements of today's equipment for the thickness of the single crystal film. The inventors of the present invention have found that nano-scale lithium niobate and lithium tantalate films have obvious advantages in miniaturization, high-frequency processing, fast speed, and energy saving of related devices. A smart stripping method (Smart cut) can be used to obtain a single crystal film with nano-level thickness. The smart stripping method can not only meet the device's requirements for the thickness of the single crystal film, but also can obtain a single crystal film with nano-level thickness without sacrificing the remaining wafer, which can significantly improve the utilization rate of the wafer and reduce production costs.

[0031] In the process of the intelligent stripping method, the oxide single crystal film is often separated after being bonded to the supporting substrate. The bonding force between the single crystal film and the substrate will directly affect the yield rate of the subsequent device preparation during the cutting process. To this end, an exemplary embodiment of the present invention provides a nanoscale single crystal film that can improve the bonding force between the single crystal film and the substrate. The nanoscale single crystal film may include a film layer, an isolation layer, and a substrate layer, wherein a first transition layer is provided between the film layer and the isolation layer, and a second transition layer is provided between the isolation layer and the substrate layer.

[0032] Hereinafter, a nanoscale single crystal thin film according to an exemplary embodiment of the present invention will be described in detail with reference to the accompanying drawings.

[0033] Figure 1 is a schematic diagram illustrating a nanoscale single crystal thin film according to an exemplary embodiment of the present invention.

[0034] Reference Figure 1 The nanoscale single crystal thin film 10 according to an exemplary embodiment of the present invention may sequentially include a thin film layer 100, a first transition layer 310, an isolation layer 400, a second transition layer 320, and a substrate layer 200. The first transition layer 310 is located between the thin film layer 100 and the isolation layer 400, and the second transition layer 320 is located between the isolation layer 400 and the substrate layer 200.

[0035] According to an exemplary embodiment of the present invention, the nanoscale single crystal thin film 10 may be prepared as a wafer, and the diameter of the wafer may be 2 inches to 12 inches.

[0036] According to an exemplary embodiment of the present invention, the thin film layer 100 is a nano-scale single crystal thin film layer and can be a piezoelectric thin film layer. The material of the thin film layer 100 can be lithium niobate, lithium tantalate or quartz. The surface of the thin film layer 100 is a polished surface. The thickness of the thin film layer 100 is 10nm to 2000nm. Preferably, the thickness of the thin film layer 100 is 10nm to 200nm, 300 to 900nm, or 900nm to 1500nm.

[0037] According to an exemplary embodiment of the present invention, the material of the substrate layer 200 may be lithium niobate, lithium tantalate, silicon, quartz, sapphire or silicon carbide. The thickness of the substrate layer 200 is 0.1 mm to 1 mm. Preferably, the thickness of the substrate layer 200 may be 0.1 mm to 0.2 mm, 0.3 mm to 0.5 mm or 0.2 mm to 0.5 mm. According to an exemplary embodiment of the present invention, the material of the substrate layer 200 may be the same as the material of the thin film layer 100. However, the invention is not limited thereto, and the material of the substrate layer 200 may be different from the material of the thin film layer 100.

[0038] According to an exemplary embodiment of the present invention, the isolation layer 400 may be a silicon dioxide layer prepared by a deposition method or an oxidation method on the substrate layer 200. The thickness of the isolation layer 400 may be 0.05 μm to 4 μm. Preferably, the thickness of the isolation layer 400 may be 0.05 μm to 0.5 μm, 0.5 μm to 1 μm, 1 μm to 2 μm, or 2 μm to 3 μm.

[0039] According to an exemplary embodiment of the present invention, the first transition layer 310 and the second transition layer 320 may be amorphous, and the thickness of the first transition layer 310 and the second transition layer 320 are different. The thickness of the first transition layer 310 is 2nm to 10nm, and the thickness of the second transition layer 320 is 0.5nm to 15nm.

[0040] According to an exemplary embodiment of the present invention, the first transition layer 310 contains a certain concentration of H element. The concentration of H element in the first transition layer 310 may be 1×10 19 / cc~1×10 22 / cc. The H element originates from the water molecules adsorbed on the surface after the plasma treatment, and can form hydrogen bonds, thereby promoting bonding and enhancing the bonding force of the nano-scale single crystal film. Therefore, by increasing the concentration of the H element in the first transition layer 310, the bonding force of the nano-scale single crystal film can be enhanced.

[0041] According to an exemplary embodiment of the present invention, the concentration of the H element in the first transition layer 310 can be increased by a variety of methods. For example, the concentration of the H element in the first transition layer 310 can be increased by extending the plasma treatment time. Specifically, the surface of the wafer (e.g., the target thin film wafer and / or the substrate wafer) can be subjected to plasma treatment for 30s to 180s, so that more active functional groups (e.g., -OH) are generated on the surface of the treated wafer, and the active functional groups can adsorb water molecules in the air to the surface of the wafer when bonding, so as to introduce the H element to the bonding surface. Preferably, the surface of the wafer can be subjected to plasma treatment for 60s to 120s.

[0042] According to another exemplary embodiment of the present invention, when plasma treatment is performed on the surface of the wafer, a high-purity gas with a slightly higher water content may be selected for plasma treatment, thereby increasing the H content in the first transition layer 310. Preferably, the water content (volume fraction) of the high-purity gas used for plasma treatment is greater than 2×10 -6 .

[0043] According to another exemplary embodiment of the present invention, the surface of the wafer after the plasma treatment may be subjected to megasonic cleaning using deionized water to increase the content of the H element in the first transition layer 310 .

[0044] According to an exemplary embodiment of the present invention, in the first transition layer 310, the concentration of the H element has a maximum concentration point, and the concentration of the H element gradually decreases from its maximum concentration point in the direction toward the thin film layer 100 and the isolation layer 400. In addition, according to an exemplary embodiment of the present invention, the first transition layer 310 and the second transition layer 320 may also contain elements used in plasma treatment, such as Ar elements, N elements, etc. Among them, the Ar, N and other elements in the second transition layer 320 are diffused from the first transition layer 310.

[0045] According to an exemplary embodiment of the present invention, the first transition layer 310 includes intrinsic elements in the thin film layer 100 and the isolation layer 400. In the first transition layer 310, the concentration of the element of the thin film layer 100 gradually decreases from the thin film layer 100 toward the isolation layer 400, and the concentration of the element of the isolation layer 400 gradually decreases from the isolation layer 400 toward the thin film layer 100. According to an exemplary embodiment of the present invention, the second transition layer 320 includes intrinsic elements in the substrate layer 200 and the isolation layer 400, and in the second transition layer 320, the concentration of the element of the substrate layer 200 gradually decreases from the substrate layer 200 toward the isolation layer 400, and the concentration of the element of the isolation layer 400 gradually decreases from the isolation layer 400 toward the substrate layer 200.

[0046] Figure 2 is shown with Figure 1 Transmission electron microscope (TEM) image of nanoscale lithium tantalate single crystal film (LTOISI) on silicon substrate corresponding to the nanoscale single crystal film. Figure 3 and Figure 4 They are Figure 2 TEM magnified images of area A and area B. Figure 5 is the secondary ion mass spectrum (SIMS) of LTOISI. Figure 6 and Figure 7 They are the element distribution maps of the bonding surface and deposition surface of LTOISI, respectively.

[0047] Figures 2 to 7The thin film layer 100 of the nanoscale lithium tantalate single crystal thin film (LTOISI) on the silicon substrate is a lithium tantalate (LiTaO3) layer, the isolation layer 400 is a silicon dioxide (SiO2) layer, and the substrate layer 200 is a silicon (Si) layer. Figure 3 It can be seen that the Figure 2 The region A at the interface between the thin film layer 100 and the isolation layer 400 includes three layers with clear interfaces, namely, the thin film layer 100, the first transition layer 310 and the isolation layer 400. Figure 4 It can be seen that the Figure 2 Region B at the interface between the isolation layer 400 and the substrate layer 200 includes three layers with clear interfaces, namely the isolation layer 400, the second transition layer 320 and the substrate layer 200, wherein the thickness of the thin film layer 100 is 300nm, the thickness of the isolation layer SiO2 is 200nm, and the thickness of the Si substrate is 0.5mm.

[0048] Reference Figure 5 , Figure 5 The area encircled by the middle circle represents the first transition layer 310 of the LTOISI. Figure 5 It can be seen that the first transition layer 310 contains a high concentration of H element, and the H element has a maximum concentration in the first transition layer 310, and the concentration of the H element decreases from the maximum concentration toward the thin film layer 100 and the isolation layer 400. The high concentration of H element in the first transition layer 310 of the LTOISI improves the bonding force of the LTOISI.

[0049] In addition, from Figure 5 It can be seen from the figure that a certain concentration of H element also exists in the second transition layer 320 between the isolation layer 400 and the substrate layer 200, which is due to the diffusion of H element caused by the annealing process.

[0050] Reference Figure 6 The thickness of the first transition layer 310 of the LTOISI is about 2 nm. In the first transition layer 310, the concentration of the Ta element of the thin film layer 100 gradually decreases from the thin film layer 100 to the isolation layer 400, and the concentration of the Si element of the isolation layer gradually decreases from the isolation layer 400 to the thin film layer 100. In addition, the bonding surface (first transition layer 310) of the LTOISI also includes the Ar element.

[0051] from Figure 7It can be seen that the thickness of the second transition layer 320 of the LTOISI is about 1 nm. In the second transition layer 320, the concentration of the O element of the isolation layer 400 gradually decreases along the direction from the isolation layer 400 to the substrate layer 200, and the concentration of the Si element of the substrate layer 200 gradually decreases along the direction from the substrate layer 200 to the isolation layer 400. In addition, in the second transition layer 320 of the LTOISI, there may also be Ar elements diffused from the first transition layer 310.

[0052] Figure 8 is shown with Figure 1 Transmission electron microscope (TEM) image of nanoscale lithium niobate single crystal film (LNOI) on lithium niobate substrate corresponding to the nanoscale single crystal film. Fig. 9 and Fig.10 They are Figure 8 TEM enlarged images of area C and area D in the figure. Fig.11 This is the secondary ion mass spectrum (SIMS) of LNOI. Fig.12 and Fig.13 These are the element distribution maps of the bonding surface and deposition surface of LNOI, respectively.

[0053] Figures 8 to 13 The thin film layer 100 of the lithium niobate single crystal thin film (LNOI) is a lithium niobate (LiNbO3) layer (ie, Fig. 9 and Fig.10 The isolation layer 400 is a silicon dioxide (SiO2) layer, and the substrate layer 200 is a lithium niobate layer. Figures 8 to 10 It can be seen that the transition layer 300 of LNOI includes a first transition layer 310 and a second transition layer 320, the thickness of the first transition layer 310 is less than the thickness of the second transition layer 320, and the interface between the thin film layer 100, the first transition layer 310, the isolation layer 400, the second transition layer 30 and the substrate layer 200 is clear, so that the scattering loss of light when propagating in the thin film can be greatly reduced, and the performance of the nano-scale single crystal thin film can be improved. In this embodiment, the thickness of the thin film layer 100 of LNOI is 500nm, the thickness of the isolation layer 400 is 2000nm, and the thickness of the substrate layer 200 is 0.35mm.

[0054] from Fig.11 It can be seen that the first transition layer 310 of the LNOI contains a high concentration of H element, and the concentration of the H element has a maximum concentration (called the maximum concentration point) within a certain depth range, and the concentration of the H element gradually decreases from the maximum concentration point toward the thin film layer 100 and the isolation layer 400, respectively.

[0055] Reference Fig.12, the thickness of the first transition layer 310 of the LNOI is about 3 nm. In the first transition layer 310 of the LNOI, the concentration of the Nb element of the thin film layer 100 gradually decreases from the thin film layer 100 to the isolation layer 400, and the concentration of the Si element of the isolation layer gradually decreases from the isolation layer 400 to the thin film layer 100. In addition, the bonding surface (first transition layer 310) of the LNOI also includes the Ar element.

[0056] Reference Fig.13 , the thickness of the second transition layer 320 of the LNOI is about 10 nm. In the second transition layer 320, the concentration of the Si element of the isolation layer 400 gradually decreases along the direction from the isolation layer 400 to the substrate layer 200, and the concentration of the Nb element of the substrate layer 200 gradually decreases along the direction from the substrate layer 200 to the isolation layer 400. In addition, the Ar element diffused from the first transition layer 310 may also exist in the second transition layer 320 of the LNOI.

[0057] In order to further verify the relationship between the H concentration in the first transition layer and the bonding force of the single crystal film, a bonding force test experiment was performed on the nanoscale single crystal film according to the exemplary embodiment. Fig.14 is a schematic diagram showing a bonding force test experiment performed on an LTOISI sample according to an exemplary embodiment.

[0058] The bonding force test experiment of nanoscale single crystal film was carried out by Czochralski method. In order to eliminate the influence of other variables, all nanoscale single crystal film samples in the bonding force test experiment were LTOISI samples, and except for the different H concentration in the first transition layer, other characteristics of the tested LTOISI samples, such as thickness, were basically the same.

[0059] Reference Fig.14 , the LTOISI samples were cut into 2cm×2cm squares, and the cut samples were placed between the clamp 1 and the clamp 4. For ease of description, only the film layer 2 and the substrate layer 3 of the LTOISI sample are shown here. The upper surface of the film layer 2 of the LTOISI sample is adhered to the lower surface of the clamp 1 by an adhesive, and the lower surface of the substrate layer 3 of the LTOISI sample is adhered to the upper surface of the clamp 4 by an adhesive. The diameters of the clamps 1 and 4 are both 1.5cm. After the adhesive is completely cured, Fig.14 As shown, a tensile force F is applied to the LTOISI sample in the vertical direction to test the tensile force required when the nanoscale single crystal film layer of the LTOISI sample falls off from the substrate layer. The greater the tensile force, the greater the bonding force of the nanoscale single crystal film sample. Table 1 shows the data of the bonding force test experiment of LTOISI samples with different H concentrations.

[0060] Table 1 Bond force test experimental data

[0061] Sample No. H concentration (atoms / cc) Tension F(N) 1 <![CDATA[9.27×10 20 ]]> 7021.48 2 <![CDATA[4.61×10 20 ]]> 5052.38 3 <![CDATA[1.55×10 20 ]]> 3124.12

[0062] As shown in Table 1, the greater the H concentration in the first transition layer, the greater the pulling force required when the thin film layer 2 of the LTOISI sample is peeled off from the substrate layer 3. Therefore, increasing the H element concentration in the first transition layer of the nanoscale single crystal film can improve the bonding force of the nanoscale single crystal film.

[0063] According to an exemplary embodiment of the present invention, a method for preparing a nanoscale single crystal thin film includes at least the following steps: (1) a process of performing ion implantation on the bonding surface of an oxide single crystal wafer (target thin film wafer) to form an ion implantation layer in the oxide single crystal wafer, (2) a process of using plasma to activate the bonding surface of the oxide single crystal wafer and a substrate wafer, (3) a process of bonding the cleaned oxide single crystal wafer and the substrate wafer at room temperature to obtain a bonded body, and (4) a process of heat treating the bonded body to peel the oxide single crystal thin film from the ion implantation layer.

[0064] A method of preparing a nanoscale single crystal thin film according to an exemplary embodiment of the present invention will be described in detail below.

[0065] First, prepare a target thin film wafer and a substrate wafer. The target thin film wafer can be a lithium niobate wafer, a lithium tantalate wafer, or a quartz wafer. The substrate wafer can be a lithium niobate wafer, a lithium tantalate wafer, a silicon wafer, a quartz wafer, a sapphire wafer, or a silicon carbide wafer. The target thin film wafer and the substrate wafer can be the same or different. The thickness of the target thin film wafer can be 100 μm to 500 μm, and the thickness of the substrate wafer can be 50 μm to 2000 μm.

[0066] Next, ions (for example, H ions or He ions) are implanted into the target thin film wafer by ion implantation, so that the target thin film wafer is formed to include a thin film layer, a separation layer and a residual material layer (the energy of the implanted ions determines the thickness of the final thin film layer). The separation layer is located between the thin film layer and the residual material layer. The thickness of the thin film layer of the nanoscale single crystal thin film to be formed can be controlled to be 10nm to 2000nm by ion implantation, and the thickness control accuracy is within 5nm. Because the amount removed by subsequent chemical mechanical polishing is very small, the deterioration effect of chemical mechanical polishing on the non-uniformity of the thin film can be fully reduced, and the uniformity of the thin film can be made less than 30nm.

[0067] Then, an isolation layer (e.g., SiO2 layer) is formed on one surface of the substrate wafer by a deposition method or an oxidation method, and the isolation layer is annealed. According to an exemplary embodiment of the present invention, an isolation layer including, for example, SiO2 can be formed by a process such as thermal oxidation or deposition, and then the isolation layer is annealed to remove internal impurities and eliminate stress. Alternatively, the isolation layer can also be chemically mechanically polished to obtain a smooth surface suitable for a direct bonding process. The isolation layer is polished to a target thickness, thereby obtaining a substrate wafer having an isolation layer of a certain thickness on the surface.

[0068] Then, the target thin film wafer and the substrate wafer are cleaned, and the surface of the target thin film wafer after cleaning, on which the thin film layer is formed (i.e., the surface of the target thin film wafer subjected to ion implantation) and the surface of the isolation layer on the substrate wafer are subjected to plasma treatment using, for example, Ar gas. The surfaces after the plasma treatment are contacted at room temperature for direct bonding to form a bonded body. The plasma surface treatment method may include radio frequency plasma treatment, jet plasma treatment, atmospheric pressure plasma treatment, etc. The bonding process may include, for example, direct bonding in an air environment, vacuum bonding, pressurized bonding, etc.

[0069] According to an exemplary embodiment of the present invention, plasma treatment activates the bonding surface, and a high bonding force can be obtained at a lower temperature. In addition, many active functional groups are generated on the plasma-treated surface, and the active functional groups can adsorb water molecules in the air to the surface, so that the H element is introduced into the bonding surface (i.e., the transition layer). The H element in the transition layer can form hydrogen bonds, thereby promoting bonding to enhance the bonding force of the bonded body. The content of the H element in the first transition layer can be increased by extending the plasma treatment time, using a gas with a high water content, and using deionized water to perform megasonic cleaning on the surface of the plasma-treated wafer to improve the bonding force of the bonded body.

[0070] Next, the bonded body is heated to separate the thin film layer and the residual material layer. According to an exemplary embodiment of the present invention, the bonded body is heated at a temperature of 100°C to 400°C, so that the ions in the implanted layer undergo a chemical reaction to become gas molecules or atoms, and generate tiny bubbles. As the heating time increases or the heating temperature increases, the bubbles will become more and more numerous and their volume will gradually increase. When these bubbles are connected into one piece, the thermal separation of the thin film layer and the residual material layer is achieved, thereby preparing an initial nanoscale single crystal thin film including a thin film layer, an isolation layer, and a substrate layer.

[0071] Next, an annealing process is performed on the obtained initial nanoscale single crystal film at a temperature of 300°C to 600°C to eliminate lattice defects introduced in the film layer due to ion implantation, and the film layer of the annealed initial nanoscale single crystal film is chemically mechanically polished to reach a predetermined thickness, thereby finally obtaining a nanoscale single crystal film.

[0072] The present invention provides a nanoscale single crystal film with reduced internal defects. The first transition layer and the second transition layer of the nanoscale single crystal film can release stress, reduce defects in the single crystal film and the isolation layer, improve the quality of the single crystal film and the isolation layer, and play a role in reducing transmission loss; in addition, releasing stress can make the medium at the interface more uniform, reduce the scattering of light during propagation, and thus reduce transmission loss.

[0073] The present invention provides a nano-scale single crystal film with increased bonding force of the single crystal film, the nano-scale single crystal film comprises a film layer with a thickness of 10nm to 2000nm and a first transition layer between the film layer and the isolation layer and containing a certain concentration of H element. Because the nano-scale single crystal film has increased bonding force, when the nano-scale single crystal film is used to prepare electronic devices such as filters, a large-area debonding phenomenon can be avoided during the cutting process, thereby improving the utilization rate of the nano-scale single crystal film and the yield rate of the electronic devices.

Claims

1. A nanoscale single crystal thin film, characterized in that: The nanoscale single crystal thin film comprises: Nanoscale single crystal thin film layers; Isolation layer; a substrate layer; and A first transition layer and a second transition layer, wherein the first transition layer is located between the nanoscale single crystal thin film layer and the isolation layer, the material of the nanoscale single crystal thin film layer is lithium niobate, lithium tantalate or quartz, and the isolation layer is a silicon dioxide layer; the second transition layer is amorphous, located between the isolation layer and the substrate layer, the material of the substrate layer is lithium niobate, lithium tantalate, silicon, quartz, sapphire or silicon carbide; The first transition layer contains a certain concentration of H element, and the concentration of H element in the first transition layer is 1×10 19 atoms / cc~1×10 22 atoms / cc, the H element in the first transition layer has a maximum concentration, and the concentration of the H element in the first transition layer gradually decreases from the maximum concentration toward the isolation layer and the nanoscale single crystal thin film layer.

2. The nanoscale single crystal thin film according to claim 1, wherein: The first buffer layer also contains elements used in the plasma treatment.

3. The nanoscale single crystal thin film according to claim 1 or 2, wherein: The first transition layer is amorphous.

4. The nanoscale single crystal thin film according to claim 1, wherein: The thickness of the nanoscale single crystal thin film layer is 10nm~2000nm.

5. The nanoscale single crystal thin film according to claim 1, wherein: The thickness of the substrate layer is 0.1 mm to 1 mm.

6. The nanoscale single crystal thin film according to claim 1, wherein: The thickness of the isolation layer is 0.05 μm to 4 μm, the thickness of the first transition layer is 2 nm to 10 nm, and the thickness of the second transition layer is 0.5 nm to 15 nm.

7. The nanoscale single crystal thin film according to claim 1 or 2, wherein: The first transition layer and the second transition layer have different thicknesses.

8. The nanoscale single crystal thin film according to claim 1, 4, 5 or 6, wherein: The material of the nanometer-scale single crystal thin film layer is the same as that of the substrate layer.

9. The nanoscale single crystal thin film according to claim 1, 4, 5 or 6, wherein: The material of the nanoscale single crystal thin film layer is different from that of the substrate layer.

10. The nanoscale single crystal thin film according to claim 1, wherein: In the direction from the nanoscale single crystal thin film layer to the isolation layer, the content of the nanoscale single crystal thin film layer elements in the first transition layer gradually decreases, and the content of the isolation layer elements gradually increases; in the direction from the isolation layer to the substrate layer, the content of the isolation layer elements in the second transition layer gradually decreases, and the content of the substrate layer elements gradually increases.

Citation Information

Patent Citations

  • Composite single crystal thin film and method for manufacturing composite single crystal thin film

    CN105321806A

  • Composite substrate, and method for manufacturing composite substrate

    JP2017139720A

  • Method for manufacturing SOI substrate

    US20080153272A1